KOMPETENSI DAN MOTIVASI SEBAGAI UPAYA MENCAPAI KEPUASAN KERJA DENGAN DIMEDIASI KINERJA PADA GURU SMA NEGERI SEKABUPATEN JEPARA - Hariyanto, 11.52.02.0022 (Students Journal of Economic and Management, 2013)
This searching has a direction for knowing and testing how far Competency and MotivationÂ influential toward job SatisfactionâsÂ with Performance mediation work dimension for all of teacher Sekolah Menengah Atas in Jepara city. Sampling was done by multiphase sampling technique. From the result of multiphase sampling, the sample was used in this study, totaling 109 people. Testing data technique which is used in this study include validity test , reliability test by Cronbach alpha formula,klasic asumtion tes: normality tes,multicolinierytas and heteroskedastisitas.F tes/ significance simultan tes.T tes/ parcial significance tes with multiple regression analysis, and significanceÂ tests, the coeffisien of Â to prove the hypothesis and mediation test1 & 2. Results of searching showed that the F tes: kompetence and motivation has positive influence and significance toward performance.Kompetence,motivation and performance has positive influence and significance toward job satisfaction too.T tes: everything hypotesis has positive influence and significance.And mediation tes variables of Performance proved to mediation Â the compentence and motivation toward job satisfactionâsÂ for all of teacher in Jepara city. Keyword : Competence. Motivation, Performenance, Job Satisfactionâs .